2014
DOI: 10.1179/2045772313y.0000000179
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin modulates TLR4/NF-κB inflammatory signaling pathway following traumatic spinal cord injury in rats

Abstract: Background: Curcumin, a polyphenolic compound extracted from the plant turmeric, has protective effects on spinal cord injury (SCI) through attenuation of inflammatory response. This study was designed to detect whether curcumin modulates toll-like receptor 4 (TLR4) and the nuclear factor-kappa B (NF-κB) inflammatory signaling pathway in the injured rat spinal cord following SCI. Methods: Adult male Sprague-Dawley rats were subjected to laminectomy at T8-T9 and compression with a vascular clip. There were thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 36 publications
(31 reference statements)
5
60
0
Order By: Relevance
“…Jin et al [22,30] showed that cur (100 mg/kg) given to animals 7 d after spinal cord hemisection reduced the cytokines TNF-a, IL-1b, and IL-6 expression, suppressed NF-kb signaling pathway activation, and decreased the severity of locomotion deficit. Similarly, cur treatment (50 mg/kg) once daily for 7 d after injury exerted an anti-inflammatory property through NF-kb signaling pathway, decreased glial scar intracellular composition GFAP expression, and improved functional recovery [31].…”
Section: Discussionmentioning
confidence: 98%
“…Jin et al [22,30] showed that cur (100 mg/kg) given to animals 7 d after spinal cord hemisection reduced the cytokines TNF-a, IL-1b, and IL-6 expression, suppressed NF-kb signaling pathway activation, and decreased the severity of locomotion deficit. Similarly, cur treatment (50 mg/kg) once daily for 7 d after injury exerted an anti-inflammatory property through NF-kb signaling pathway, decreased glial scar intracellular composition GFAP expression, and improved functional recovery [31].…”
Section: Discussionmentioning
confidence: 98%
“…Toll‐like receptors (TLRs) are a kind of trans‐membrane proteins and signal transduction molecules . TLR4 is a pattern recognition receptor, typically known to play a major role in generating an inflammatory response by way of distinguishing exogenous pathogen‐associated and endogenous damage‐associated molecular patterns .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Toll-like receptors (TLRs) are a kind of trans-membrane proteins and signal transduction molecules. 12 TLR4 is a pattern recognition receptor, typically known to play a major role in generating an inflammatory response by way of distinguishing exogenous pathogenassociated and endogenous damage-associated molecular patterns. 13 The effects of TLR4 and NF-κB signaling pathway in several types of tissues have been highlighted in previous studies, including liver and pancreas tissues.…”
mentioning
confidence: 99%
“…Recently, Cur has been shown to exhibit proven therapeutic benefits (including antioxidant, anti-inflammatory, anti-cancer and anti-fibrotic effects) in many pathological conditions, such as Alzheimer' s disease, Parkinson' s disease, multiple sclerosis, epilepsy, cerebral injury, cancer, allergy, asthma, bronchitis, colitis, rheumatoid arthritis, renal ischemia, psoriasis, scleroderma, diabetes, obesity, depression, fatigue and acquired immunodeficiency disease 6,7,8 . Specifically regarding the CNS, Cur was capable of providing neuroprotection after spinal cord injury, inhibiting apoptosis and neuron loss and attenuating oxidative stress in astrocytes and reactive astrogliosis 9,10,11,12,13 , suggesting that Cur might beneficially affect astrocyte population in the CNS inflammatory environment by regulating both NF-κβ and SOX9 signaling pathways 14,15 . In this context, the aim of this study was to evaluate whether Cur had the capacity to affect astrocyte response during the process of demyelination and remyelination following gliotoxic injury induced by ethidium bromide (EB).…”
mentioning
confidence: 99%